Observer-Based Mixed ℋ2/ℋ∞ Tracking Control for Continuous-Time Systems with Integral Action and Pole Placement - Huxiong Li (Discrete Dynamics in Nature and Society)
The tracking problem for continuous-time systems is investigated. It is assumed that the states of the systems are not available. An observer is firstly designed to estimate the states by using the ℋ∞ method. The control action is consist of a state-feedback control, an integral component, and a feedforward loop. The linear-matrix-inequality region is used to constrain the eigenvalue location for the closed-loop systems. The control gains can be obtained by solving a sequence of linear matrix inequalities (LMIs) which can guarantee the mixed ℋ2/ℋ∞ performance for the closed-loop systems.